Decisive Procedures Used in Domestic Crises Management during Hybrid War (2) - Marinescu, Emanuel Stefan; Sirbu, Gabriela Elena (Acta Universitatis Danubius. Relationes Internationales, 2023)
Nowadays, in the aggressive approach being involved highly technical structures, with massive combat potential, benefiting from ample support, materialized in all action environments, the hybrid confrontation has become a certainty. As a result, countermeasure concerns must be well known at all levels, primarily in the tactical space. So, the factors involved in internal crisis management will be responsible for the preparation and application of high-value procedures that can lead to the achievement of the proposed security goals. It is necessary that the combat reactions at each facility be synchronized with the efforts of the hierarchically higher levels, undertaken in various spaces or connected with the concerns of the force institutions. This way, it is possible to achieve desired goals, to maintain the security of the objectives, in relation to the diversity of forms of aggression considered by a potential aggressor.